Neonatal amygdala lesions alter mother–infant interactions in rhesus monkeys living in a species‐typical social environment. Issue 8 (2nd July 2014) - Raper, Jessica; Stephens, Shannon B.Z.; Sanchez, Mar; Bachevalier, Jocelyne; Wallen, Kim; Sullivan, Regina M.
ABSTRACT The current study examined the effects of neonatal amygdala lesions on mother–infant interactions in rhesus monkeys reared in large species‐typical social groups. Focal observations of mother–infant interactions were collected in their social group for the first 12 months postpartum on infants that had received amygdala lesions (Neo‐A) at 24–25 days of age and control infants. Early amygdala lesions resulted in subtle behavioral alterations. Neo‐A females exhibited earlier emergence of independence from the mother than did control females, spending more time away from their mother, whereas Neo‐A males did not. Also, a set of behaviors, including coo vocalizations, time in contact, and time away from the mother, accurately discriminated Neo‐A females from control females, but not Neo‐A and control males. Data suggest that neonatal amygdalectomy either reduced fear, therefore increasing exploration in females, or reduced the positive reward value of maternal contact. Unlike females, neonatal amygdala lesions had little measurable effects on male mother–infant interactions. The source of this sex difference is unknown. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1711–1722, 2014.